THE EFFECT OF ROTATION AND TEMPERATURE ON THE INHIBITION PERFORMANCE OF CASHEW (ANACARDIUM OCCIDENTALE L.) NUT SHELL LIQUID ON CO2 CORROSION OF CARBON STEEL - Buchweishaija, J.; Mkayula, L. L (Tanzania Journal of Engineering and Technology, 2018)
A natural extract of cashew nut shells, Cashew Nut Shell Liquid (CNSL) was investigated as a corrosion inhibitor for carbon steel in 3% NaCl solutions saturated with CO 2 gas using electrochemical techniques (i.e. potentiodynamic polarization and ac-impedance). The investigation was performed at different temperatures under static and dynamic conditions using a Rotating Disk Electrode (RDE). It was found that CNSL reduces the electrochemical processes taking place on carbon steel undergoing corrosion. The percentage inhibitor efficiency increases with increase in CNSL concentration and decreases with rise in temperature. Better performance at low CNSL concentration was registered under dynamic conditions and room temperatures. Thus CNSL is a potential corrosion inhibitor for carbon steel undergoing corrosion in CO2 medium.